Application specific intensity distributions for laser materials processing: Tailoring the induced temperature profile. (December 2018) - Völl, Annika; Vogt, Sabrina; Wester, Rolf; Stollenwerk, Jochen; Loosen, Peter
Highlights: Efficient computation of adapted intensity distributions in materials processing. Solution of an inverse heat conduction problem in 3D. Exemplary results for laser softening and laser transmission welding. Generation of adapted intensity distributions using freeform optics. Validation using commercial ray-tracing and FEM software. Abstract: In laser materials processing the intensity distribution of the laser beam strongly influences the spatial and temporal temperature profile that is induced within the treated material and therefore the shape of the heat influenced zone. As a consequence, the processing quality and efficiency can be increased by using adapted intensity distributions that explicitly tailor the generated temperature profile. In this work, an efficient numerical method to calculate application specific intensity distributions is presented that induce prescribed spatial and temporal temperature profiles in the material. To this end, this task is described as an inverse heat conduction problem which is solved with the conjugate gradient method with adjoint problem. As temperature-dependent thermo-physical material properties, volumetric beam absorption and quasi-stationary distributions can be accounted for, this approach proves to be very general. The performance of the algorithm is then shown by presenting two different test cases. While the first one is taken from the application of laser softening, the second one simulates a time-dependent intensity distribution for laser transmission welding. Furthermore, ideas how to implement the obtained intensity distributions, which are very inhomogeneous, are provided using specialized beam shaping techniques. The results for both test cases are validated using commercial FEM solvers.